The Influence of Customer Capital and Service Capital on the Intellectual Capital That Has an Impact on the Village Apparatus - Hamdani, Deky; Ayu Esteka Sari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of Customer Capital and Service Capital on Intellectual Capital and its impact on the performance of village apparatus in Sungai TFull City. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method to test the relationship between variables. Data was collected through a survey with a questionnaire distributed to village officials in Sungai TFull City. The population in this study is all village apparatus in Sungai TFull City, while the sample was selected using purposive sampling, with a total of 100 respondents who met certain criteria, such as work experience and involvement in village public services. The results show that Customer Capital and Service Capital have a significant effect on Intellectual Capital with coefficients of 0.475 and 0.496, respectively. Intellectual Capital also contributed 0.333 to improving the performance of village apparatus. In addition, Service Capital and Customer Capital have a direct influence on performance with coefficients of 0.206 and 0.178, although the largest influence on performance comes from Intellectual Capital. The analysis of direct and indirect effects shows that Intellectual Capital plays a mediating variable in the relationship between Customer Capital and Service Capital and the performance of village officials. The indirect effect of Service Capital and Customer Capital on performance through Intellectual Capital was 0.207 and 0.208, respectively.